Sheltered adolescents’ background of exposure to violence and distressful experiences - Ramos, Kézia Áurea de Almeida; Rafael, Ricardo de Mattos Russo; Penna, Lucia Helena Garcia; Depret, Davi Gomes; Ribeiro, Liana Viana; Carinhanha, Joana Iabrudi (Revista Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to analyze the exposure to violence and distressful experiences lived by adolescents in institutional shelters in the city of Rio de Janeiro (previous to their admittance). Methods: a cross-sectional study carried out in public institutional shelter units, with a sample of 72 adolescents aged between 12 and 18 years. Data on sociodemographic aspects, family relationships and distressful experiences were obtained by means of the Parcours Amoureux des Jeunes instrument, validated for use in Brazil. Statistical analysis included estimates of prevalence and 95% confidence intervals. Results: high magnitudes of distressful experiences and overlapping abuses lived by adolescents were observed, especially violent events (72.2%), social exclusion (59.1%), and sexual harassment (48.6%). Conclusions: the study shows that adolescents under institutional sheltering come from a background of severe and frequent distressful experiences. These took place in multiple environments: family (prior to their institutional reception), community, and group.